Intercomparison of Hantzsch and fiber-laser-induced-fluorescence formaldehyde measurements - Jennifer Kaiser; Xin Li; Ralf Tillmann; Ismail-Hakki Acir; Holland, Frank; Rohrer, Franz; Robert Wegener; Keutsch, Frank N (Atmospheric Measurement Techniques, 2014)
Two gas-phase formaldehyde (HCHO) measurement techniques, a modified commercial wet-chemical instrument based on Hantzsch fluorimetry and a custom-built instrument based on fiber laser-induced fluorescence (FILIF), were deployed at the atmospheric simulation chamber SAPHIR (Simulation of Atmospheric PHotochemistry In a large Reaction Chamber) to compare the instruments' performances under a range of conditions. Thermolysis of para-HCHO and ozonolysis of 1-butene were used as HCHO sources, allowing for calculations of theoretical HCHO mixing ratios. Calculated HCHO mixing ratios are compared to measurements, and the two measurements are also compared. Experiments were repeated under dry and humid conditions (RH < 2% and RH > 60 %) to investigate the possibility of a water artifact in the FILIF measurements. The ozonolysis of 1-butene also allowed for the investigation of an ozone artifact seen in some Hantzsch measurements in previous intercomparisons. Results show that under all conditions the two techniques are well correlated (R-2 >= 0.997), and linear regression statistics show measurements agree with within stated uncertainty (15% FILIF + 5% Hantzsch). No water or ozone artifacts are identified. While a slight curvature is observed in some Hantzsch vs. FILIF regressions, the potential for variable instrument sensitivity cannot be attributed to a single instrument at this time. Measurements at low concentrations highlight the need for a secondary method for testing the purity of air used in instrument zeroing and the need for further FILIF White cell outgassing experiments